2022
DOI: 10.1158/1541-7786.mcr-22-0139
|View full text |Cite
|
Sign up to set email alerts
|

CBX8 Together with SET Facilitates Ovarian Carcinoma Growth and Metastasis by Suppressing the Transcription of SUSD2

Abstract: Polycomb group proteins are often dysregulated in cancer, leading to disruption of epigenetic landscapes and acquisition of cancer hallmarks. Chromobox 8 (CBX8) is a core component of canonical polycomb repressive complex 1, however, its role in transcriptional regulation and in ovarian carcinoma progression has not been extensively investigated. In this study, we find that CBX8 is up-regulated in ovarian cancer. Overexpression and knockdown approaches show that CBX8 facilitates the growth and migration of CAO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The versatile protein SET is involved in multiple cellular functions, such as apoptosis, transcription, nucleosome assembly, and histone chaperoning [ 29 ]. Isoform 2 of SET functions to inhibit apoptosis by blocking the activity of GZMA-activated DNase NME1.During cytotoxic T lymphocyte-induced cell death, GZMA cuts SET, breaking its connection with NME1 and releasing the suppression of NME1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The versatile protein SET is involved in multiple cellular functions, such as apoptosis, transcription, nucleosome assembly, and histone chaperoning [ 29 ]. Isoform 2 of SET functions to inhibit apoptosis by blocking the activity of GZMA-activated DNase NME1.During cytotoxic T lymphocyte-induced cell death, GZMA cuts SET, breaking its connection with NME1 and releasing the suppression of NME1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The versatile protein SET is involved in multiple cellular functions, such as apoptosis, transcription, nucleosome assembly, and histone chaperoning [ 29 ]. Isoform 2 of SET functions to inhibit apoptosis by blocking the activity of GZMA-activated DNase NME1.During cytotoxic T lymphocyte-induced cell death, GZMA cuts SET, breaking its connection with NME1 and releasing the suppression of NME1 [ 29 ]. Both isoforms 1 and 2 function as strong blockers of phosphatase 2A.Isoforms 1 and 2 also hinder EP300/CREBBP- and PCAF-mediated histone acetyltransferases and nucleosomes, possibly by blocking the access of histone lysine residues to acetylases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBX8 is involved in the progression of glioblastoma and breast cancer (Jia et al, 2020). Our previous work has demonstrated that CBX8, together with SET, promotes ovarian carcinoma growth and metastasis by downregulating SUSD2 expression (Creppe et al, 2014; Wu et al, 2022). To gain a comprehensive understanding of different functions of CBX proteins in cancer progression, we investigated the mRNA expression of these five CBX family genes across multiple cancers using TCGA data set.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression and knockdown experiments have indicated that CBX8 promotes the growth and migration of OC cells in vitro. Mechanistically, CBX8 and SE translocation protein (SET) bind the promoter of sushi domain containing 2 (SUSD2) to establish H2AK119ub1 and block the acetylation of histone H3, resulting in the transcriptional inhibition of SUSD2 (136). 135) interacting with HDAC2 to increase the acetylation of histone H3 and H4 at the E-cadherin promoter OC Growth; migration CBX8 and SET bind to the promoter of SUSD2 to establish (136) H2AK119ub1 and block the acetylation of histone H3, resulting in transcriptional inhibition of SUSD2 CBX, chromobox; PCa, prostate carcinoma; GC, gastric cancer; CCCA, cholangiocellular carcinoma; NEPC, neuroendocrine prostate cancer; BC, breast cancer; HCC, hepatocellular carcinoma; CRC, colorectal cancer; ccRCC, clear cell renal cell carcinoma; TCA, thyroid carcinoma; OC, ovarian cancer; EMT, epithelial to mesenchymal transition; H3K9, histone H3 lysine K9; H3K4me3, histone H3 lysine K4 trimethylation; CDC20, cell division cycle 20; SFRP1, secreted frizzled-related protein 1; AR, androgen receptor; RE1, repressor element-1; TF, transcription factor; BMP4, bone morphogenetic protein 4; RUNX2, runt-related transcription factor 2; HDAC, histone deacetylase; KLF6, Kruppel-like factor 6; SET, SE translocation protein; SUSD2, sushi domain containing 2; H2AK119ub1, monoubiquitination of histone H2A lysine 119.…”
Section: Cbxs Regulate Biological Tumor Processes Through Epigenetic ...mentioning
confidence: 99%